Impact of irrigation on cropland yield potential and scenario-based optimization in Northeast China - Jiahui Li; Xinliang Xu; Luo Liu; Xiaojuan Deng; Shihao Wang (Agricultural Water Management)
As a key region for national food security, Northeast China (NEC) is under growing pressure to balance agricultural productivity and water availability amid global climate change and rising food demand. These challenges underscore the need for efficient, spatially targeted irrigation strategies to optimize water use and sustain crop production. In this study, we apply the Global Agro-Ecological Zones (GAEZ) model to assess the impacts of climate change and irrigation on yield potential dynamics across NEC from 2000 to 2020. We further conduct multi-scenario analysis to explore the outcomes of increasing irrigated area proportion by 10 %, 30 %, and 50 %, evaluating their effects on yield gap closure and climate change mitigation. Our results show an average annual increase in yield potential of 56.36 kg·ha−1·a−1 across the region. Climate change caused a 1.23 % loss in multi-year total yield potential, with 68.28 % of these losses occurring in rainfed areas, while 80.54 % of yield gains were observed in irrigated areas. Except for rice, which experienced moderate gains (49.31 kg·ha⁻¹ annually), other major crops—particularly maize and soybeans—were negatively affected by climate trends. Irrigation offset nearly 4.81 times the total climate-induced yield losses, although its positive impact has declined over time. Among the scenarios, a 30 % increase in irrigated area proportion demonstrated the greatest potential, particularly for maize. Under this scenario, yield gaps could be closed and climate-induced losses fully compensated in 16.32 % and 17.82 % of NEC croplands, respectively, primarily in the southern Songnen Plain, Liao River Plain and Greater Khingan Mountains Region. These findings provide a scientific basis for optimizing irrigation strategies to ensure food security and promote sustainable water resource management.